1981
DOI: 10.1111/j.1398-9995.1981.tb01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Suppression of Antibody Production with the Aid of Radiolabelled Birch Pollen Allergen

Abstract: In accordance with the clonal selection theory we intended to prevent the development of artificially induced birch pollen allergy in rabbits with the aid of the radiolabelled pollen allergen (75-1000 microCi125 I-pollen/animal) intravenously administered prior to pollen sensitization. The birch pollen allergen, is accordance with Burnet's working hypothesis, reacts only with a genetically determining B cell subpopulation. The fixation of the radiolabelled birch pollen allergen to the receptors of the competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Recently, Filipp et al [6] reported an extensive and selective suppression of reagin-like PCA antibodies and haemagglutinating antibodies in the blood and in nasal secretion in rabbits using of heavily labelled l25I-birch pollen allergen for immunization.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Filipp et al [6] reported an extensive and selective suppression of reagin-like PCA antibodies and haemagglutinating antibodies in the blood and in nasal secretion in rabbits using of heavily labelled l25I-birch pollen allergen for immunization.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, evidence has been presented to show an extensive suppression of different experimental im munological disorders [1][2][3][4][5][6] by-using heavily labelled allergen or antigen. We have shown the suppressing effect of 125I-ovalbumin (OA) antigen on reagin-like antibody formation by inactivation and, in this way, achieving an almost complete inhibition of anaphylac tic shock in guinea pigs [7], This phenomenon was found to be specific [7].…”
Section: Introductionmentioning
confidence: 99%
“…Passive immunization has been suggested by several authors, and is discussed below, as it is based on the observation that an IgG response develops during IT. Another example from this field is the concept (borrowed from oncology) of an "allergic bullet", a strongly radiolabelled allergen molecule that destroys the immunocompetent cells by which it is recognized (20). More delicate procedures involve in vitro boosting of T-suppressor lymphocytes (98) or administration of allergen in conjugation with IgE-restricted lymphokines (36) selectively suppressing the synthesis of specific IgE.…”
mentioning
confidence: 99%